Сарапульские подранки: повесть о юности / Р. Н. Заппаров - Заппаров Растем Нургаянович (Издательство ИжГТУ, 2005)
Экземпляры: (20200715) / Инвентарный номер: 31654 / Цена: 100.00 / Авт.знак: З-33 / ГРНТИ: 17.82.90 / ББК: 63.3(2Рос.Удм)6